Translational Control in Cancer - Robichaud, Nathaniel (Cold Spring Harb Perspect Biol, 2019)
The translation of messenger RNAs (mRNAs) into proteins is a key event in the regulation of gene expression. This is especially true in the cancer setting, as many oncogenes and transforming events are regulated at this level. Cancer-promoting factors that are translationally regulated include cyclins, antiapoptotic factors, proangiogenic factors, regulators of cell metabolism, prometastatic factors, immune modulators, and proteins involved in DNA repair. This review discusses the diverse means by which cancer cells deregulate and reprogram translation, and the resulting oncogenic impacts, providing insights into the complexity of translational control in cancer and its targeting for cancer therapy.